Gene expression profile of endometrial carcinoma cells exposed to di-(2-ethylhexyl) phthalate - Cho, Hyun-Hee; Song, Mee; Ryu, Jae Chun (KOREAN SOCIETY TOXICOGENOMICS & TOXICOPROTEOMICS-KSTT, 2013)
To evaluation of the contribution of DEHP (di-(2-ethylhexyl) phthalate) to the pathophysiology of endometriosis, ECC-1 (human endometrial cancer) cell lines were subjected to DEHP for 48h with 50 mu M DEHP and total RNA was extracted. Quantified spectro-photometrically, and RNA quality was verified via agarose-gel electrophoresis. Gene expression changes were analyzed using oligonucleotide microarray hybridization by comparing the treated and control groups (two-fold change, P< 0.05). Three independent samples were analyzed. Data indicated that 522 genes were up-regulated and 379 were down-regulated. These genes were classified according to the GO terms of biological processes and the KEGG pathway. Among biologic processes, regulation of cell death, lipid metabolism, gluconeogenesis, response to hormone stimulus, and regulation of cell differentiation were positively associated with up-regulated genes. Mitosis, meiosis, DNA damage check point, anatomical structure development, reproductive development, and regulation of protein ubiquitination were significantly associated with down-regulated genes. In the KEGG pathway analysis, the MAPK, VEGF, p53, Erbb, mTOR, and phosphatidylinositol signaling pathways were positively associated with up-regulated genes. The cell cycle, oocyte meiosis, spliceosome, and pyrimidine metabolism were positively associated with down-regulated genes. In conclusion, After DEHP treatment, some genes associated with cell growth, cell differentiation, meiosis, migration, apoptosis, and the pathophysiology of endometriosis were up regulated.